ANALISIS USAHA ALAT TANGKAP CANTRANG (BOAT SEINE) DI PELABUHAN PERIKANAN PANTAI TAWANG KABUPATEN KENDAL - Wardhani, Ratih; -, Ismail; Rosyid, Abdul (Fakultas Perikanan dan Ilmu Kelautan, Universitas Diponegoro, 2012)
Information of fishermen income level are very needed to reach the welfare population especially fishermen. Fisheries effort that will be run by businessman has to produce a suistainable profit. Therefore, it needs to be evaluated by effort analysis. The purpose of this study was to analyze the feasibility of Denish seine’s fishermen in Tawang’s coastal fishing port, Kendal region. This research was conducted on Mei 2012 in Tawang’s coastal fishing port. The methodology that used in this research is descriptive method by observation survey. It was conducted to obtain the facts, both about the social, economic, political of population or region. The determination of the samples for this research based on Arikunto (2002) is equal 42 samples.This effort analyse used discounted criterion method. From this method, we got NPV Ratio valueable mean Rp13.504.227,58 (NPV is positive), B/C Ratio valueable mean 1,02 (B/C > 1) and IRR valueable mean 23,74 %, it means Denish seine’s effort in Tawang’s coastal fishing port is feasible to continue.